2015
DOI: 10.1103/physrevb.92.064420
|View full text |Cite
|
Sign up to set email alerts
|

Shape-dependent exchange bias effect in magnetic nanoparticles with core-shell morphology

Abstract: We study the low-temperature isothermal magnetic hysteresis of cubical and spherical nanoparticles with ferromagnetic (FM) core -antiferromagnetic (AF) shell morphology, in order to elucidate the sensitivity of the exchange bias effect to the shape of the particles and the structural imperfections at the core-shell interface. We model the magnetic structure using a classical Heisenberg Hamiltonian with uniaxial anisotropy and simulate the hysteresis loop using the Metropolis Monte Carlo algorithm. For nanopart… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 24 publications
0
30
0
4
Order By: Relevance
“…Although the core was fixed at 8 nm in our core–shell nanoparticles, the shell thickness was varied, which results in varied stress values on core leading to different interfacial defects and, hence, different quantities of spin-glass clusters. In addition, it was reported that surface spins in γ-Fe 2 O 3 nanoparticles are more magnetically disordered than in Fe 3 O 4 nanoparticles of the same size [25,26,27], and thus we expect larger amount of interfacial spin-glass as the shell thickness increases.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the core was fixed at 8 nm in our core–shell nanoparticles, the shell thickness was varied, which results in varied stress values on core leading to different interfacial defects and, hence, different quantities of spin-glass clusters. In addition, it was reported that surface spins in γ-Fe 2 O 3 nanoparticles are more magnetically disordered than in Fe 3 O 4 nanoparticles of the same size [25,26,27], and thus we expect larger amount of interfacial spin-glass as the shell thickness increases.…”
Section: Discussionmentioning
confidence: 92%
“…In the case of core–shell nanoparticles, the interface atoms have a different environment than those in the core of the particle. The exchange bias is suggested to be influenced by several effects, such as the area of the core–shell interface [26], the roughness of the core–shell interface [27], the thickness of the shell [28], and the competition between the magnetostatic anisotropy and the exchange coupling [27]. The magnetic properties of Fe 3 O 4 –γ-Fe 2 O 3 core–shell nanoparticles are not well-investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, iron/iron oxide core/shell nanoparticle systems have been exploited for such applications because the combination of the high magnetization of the core (Fe) and the chemical stability and biocompatibility of the shell (Fe 3 O 4 or γ-Fe 2 O 3 ) lead to more suitable overall properties than either material alone [24,25,26]. These systems also provide excellent models for probing the roles played by interface and surface spins and their impacts on EB in exchange-coupled nanostructures, inspiring a large body of work on core/shell Fe/γ-Fe 2 O 3 [27,28,29], Fe/Fe 3 O 4 [30,31], FeO/Fe 3 O 4 [32,33,34], Fe 3 O 4 /γ-Fe 2 O 3 [35], γ-Fe 2 O 3 /CoO [36], and Au/Fe 3 O 4 particles [37,38,39]. Oxidization-driven migration of metal atoms from the core to the shell of iron/iron oxide nanoparticle systems has been shown to occur via the Kirkendall effect, leading to a morphological transformation into hollow nanoparticles, where the additional (inner) surface area strongly affects magnetic properties including EB [40,41,42,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…In order to simulate particles with rough interfaces we use a method very similar to those utilized in previous works [25,29]. Namely, for a given shell thickness and particle radius, we determine the radius R C of the ferromagnetic core.…”
Section: Nanoparticles With Roughened Interfacementioning
confidence: 99%
“…They showed that the magnitude of exchange bias is strongly correlated with the degree of roughness. Moreover, in a very recent paper, Dimitriadis et al [29] simulated cubic and spherical particles showing exchange bias phenomenon. According to their results, in terms of exchange bias characters, the distinction between cubic and spherical particles is lost for moderate roughness.…”
Section: Introductionmentioning
confidence: 99%